2019
DOI: 10.3389/fpsyg.2019.01590
|View full text |Cite
|
Sign up to set email alerts
|

Economic Inequality and Masculinity–Femininity: The Prevailing Perceived Traits in Higher Unequal Contexts Are Masculine

Abstract: Previous studies have shown that economic inequality influences psychological processes. In this article, we argue that economic inequality also makes masculine attributes more prototypical. In Study 1 ( N = 106), using an experimental design, we showed that individuals belonging to a society characterized by a higher level of economic inequality are perceived as more masculine than feminine. Study 2 ( N = 75) shows, also experimentally, that the upper social class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 49 publications
(69 reference statements)
4
28
0
2
Order By: Relevance
“…Although we use perceived competition as an explanatory mechanism, our findings are compatible with previous research about inequality and perceptions of the normative climate. For instance, individuals believed that people living in more unequal societies are more masculine, prioritize individual goals and endorse more self-enhancement values (Moreno-Bella et al, 2019;Sánchez-Rodríguez et al, 2019c;Sánchez-Rodríguez et al, 2020). These results also imply that individuals consider people in a high-inequality environment to be more threatening than those in a low-inequality environment.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although we use perceived competition as an explanatory mechanism, our findings are compatible with previous research about inequality and perceptions of the normative climate. For instance, individuals believed that people living in more unequal societies are more masculine, prioritize individual goals and endorse more self-enhancement values (Moreno-Bella et al, 2019;Sánchez-Rodríguez et al, 2019c;Sánchez-Rodríguez et al, 2020). These results also imply that individuals consider people in a high-inequality environment to be more threatening than those in a low-inequality environment.…”
Section: Discussionmentioning
confidence: 93%
“…Although no prior empirical studies examined the effect of economic inequality on social vigilance, indirect evidence supports this idea. For example, individuals living in a highly unequal society were perceived as more prototypically masculine than feminine (Moreno-Bella et al, 2019). Masculinity was generally related to self-directed and aggressive tendencies, whereas femininity was generally associated with being tender and caring about others' needs and well-being (Annandale & Hunt, 1990;Weisgram et al, 2011).…”
Section: Economic Inequality Perceived Competition and Social Vigilancementioning
confidence: 99%
“…However, the particular features attributed to a context with a specific level of economic inequality have received little attention in the literature. Only a few previous researchers have shown that a higher level of economic inequality provides a context with a masculine, individualist, and competitive normative climate (Moreno-Bella et al, 2019;Sánchez-Rodríguez, Willis, Jetten, & Rodríguez-Bailón, 2019).…”
Section: Group Processes and Intergroup Relationsmentioning
confidence: 99%
“…In most countries over the world, economic inequality has increased in recent decades (Alvaredo et al, 2018;Piketty, 2014). A large body of research has explored how economic inequality affects social and psychological responses (Jetten, 2019;Lynch et al, 2004;Moreno-Bella, Willis, & Moya, 2019;Petkanopoulou, et al, 2018;Snowdon, 2010;Wilkinson & Pickett, 2006). It has been shown that economic inequality may affect those higher and lower in wealth albeit in different ways.…”
mentioning
confidence: 99%